SAT0095 A perceived biological cause of rheumatoid arthritisonset is associated with lower levels of depressed and anxious mood over one year compared to patients who attributed onset to other causes. (12th June 2018) - Gwinnutt, J.; Verstappen, S.; Hyrich, K.; Lunt, M.; Barton, A.; Cordingley, L.; ,
Abstract : Background: Patients with rheumatoid arthritis (RA) attribute onset of their condition to a range of causes including biological, psychological, work-related causes or stressful life events. Causal attributions are associated with a range of short- and long-term outcomes. Objectives: To compare the 1 year outcomes of early RA patients who attribute a biological cause of onset of RA with patients who perceive non-biological causal attributions. Methods: The Rheumatoid Arthritis Medication Study (RAMS) is a prospective cohort of patients with RA starting methotrexate for the first time in the United Kingdom. Demographic and clinical data (pain and fatigue visual analogue scales [VAS-pain/VAS-fatigue], disease activity [DAS28], the Hospital Anxiety and Depression Scale [HADS-A, HADS-D] and the Health Assessment Questionnaire [HAQ]) were collected at baseline and 1 year later. At baseline, patients completed the Brief Illness Perception Questionnaire (Brief IPQ), which assesses key beliefs about the impact, controllability, and chronicity of RA. The final item of the Brief IPQ asks patients to report the most important factor they believe caused their disease. These causal attributions were coded as either biological (e.g. age, genetics) or other causes (e.g. work related, stressful life event). Brief IPQ item response scores were compared between these groups using linear regression, adjusted for age and gender. HAQ, DAS28, VAS-pain, VAS-fatigue, HAD-A and HADS-D over follow-up were compared between the two groups using random effects models. Results: Of 1171 patients, 483 (41.2%) reported a biological cause to be the most important factor in causing their arthritis and 688 (58.8%) reported a non-biological cause. Patients who believed in biological causes were younger (median 58 vs. 61 years; p=0.003) and more likely to be women (72.1% vs. 59.2%; p<0.001). Other baseline characteristics were similar (Table). Patients who perceived biological causes reported significantly lower concerns about their illness (median: 8 vs. 9; p=0.004) and significantly lower emotional impact (median: 5 vs. 6; p<0.001). Over follow-up, patients who attributed biological causes reported lower depression and anxiety HADS scores than those holding non-biological attributions (mean difference [95% CI]: HADS-D=−0.76 [-1.19, –0.33]; HADS-A=−0.94 [-1.41, –0.47]). Other outcomes over follow-up were similar. Conclusions: Different causal attributions of RA are associated with different outcomes and may suggest that education about RA causality could improve patient-centred outcomes; however, that would require further evaluation. Disclosure of Interest: None declared